2018
DOI: 10.1111/zph.12477
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological evaluation of Leishmania infantum zoonotic transmission risk in the recently established endemic area of Northwestern Italy

Abstract: Leishmania infantum infection had been expanding into new areas due to changes in vector and host biology. Zoonotic visceral leishmaniasis has become endemic in previously unsuitable areas as vectors find favourable climatic conditions and an increasing number of reservoir dogs are moved between traditionally and new endemic areas. Monitoring vector and disease expansion in areas of recent colonization is needed to understand transmission mechanisms and patterns of disease establishment. Here, we studied the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
3
12
1
2
Order By: Relevance
“…The occurrence of L. infantum has been largely assessed in free-ranging carnivorans, especially in canids, due to their phylogenetic closeness to dogs that are the main reservoir of this parasite (20). The prevalence of L. infantum found in foxes in this study, although lower than reported previously in Central and Southern Italy (74,75), confirms the recently established endemic area of transmission in Northern Italy where autochthonous dogs showed more than 40% of seroprevalence (24). The prevalence in foxes from Spain ranges from 14% (76) to 75% (77), while in Portugal the prevalence is much lower (78,79).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The occurrence of L. infantum has been largely assessed in free-ranging carnivorans, especially in canids, due to their phylogenetic closeness to dogs that are the main reservoir of this parasite (20). The prevalence of L. infantum found in foxes in this study, although lower than reported previously in Central and Southern Italy (74,75), confirms the recently established endemic area of transmission in Northern Italy where autochthonous dogs showed more than 40% of seroprevalence (24). The prevalence in foxes from Spain ranges from 14% (76) to 75% (77), while in Portugal the prevalence is much lower (78,79).…”
Section: Discussionsupporting
confidence: 81%
“…and L. infantum) in free-ranging canids and mustelids in the alpine area of Northwest Italy. Notably, these pathogens were chosen due to their significant impact on human and/or animal health, and for their emergence in the studied area (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in line with previous evidence reporting that many cases of Leishmania infection are asymptomatic in the Mediterranean Europe. 2,[9][10][11][12][13][14]16,17,[19][20][21][22] Some patients with subclinical infection can harbor viable parasites throughout life and may develop reactivation to full-blown visceral leishmaniasis if immunosuppression occurs thereafter. 23 Visceral and cutaneous leishmaniasis are compulsory notifiable diseases in Italy and confirmed cases are obligatorily reported by local public health departments to the regional health authorities.…”
Section: Discussionmentioning
confidence: 99%
“…Thought the distribution of Leishmania spp. consists typically of tropical and subtropical regions, these parasites are expanding to new areas, e.g., within Central Europe and the Americas (Dantas-Torres et al 2012;Ferroglio et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At least 2.5 million dogs are infected with L. infantum in southwestern Europe (Moreno and Alvar 2002;Baneth et al 2008;Pennisi 2015) as well as various species of sylvatic hosts (Molina et al 2012;Ferroglio et al 2018).…”
Section: Introductionmentioning
confidence: 99%